A Review of the Risk Factors Associated with Endometrial Hyperplasia During Perimenopause - Wang L; Wei W; Cai M (Dove Medical Press, 2024)
Lianping Wang,1 Wengong Wei,2 Meiling Cai2 1Nursing Department, Qingpu Branch, Zhongshan Hospital, Fudan University, Shanghai, 201700, People's Republic of China; 2Department of Obstetrics and Gynecology, Qingpu Branch, Zhongshan Hospital, Fudan University, Shanghai, 201700, People's Republic of ChinaCorrespondence: Meiling Cai, Department of Obstetrics and Gynecology, Qingpu Branch, Zhongshan Hospital, Fudan University, Shanghai, 201700, People's Republic of China, Tel +8618116016012, Email cai.meiling@qphospital.coBackground: Endometrial hyperplasia, characterized by excessive growth leading to endometrial thickening, is commonly observed in the premenopausal period. Its prevalence in postmenopausal women is approximately 15%, peaking between ages 50 and 60. This condition often manifests as abnormal uterine bleeding and can progress to malignancy, with varying risks depending on the type of hyperplasia.Purpose: This study aims to investigate the factors influencing endometrial thickness during the perimenopausal period and raise awareness among healthcare professionals about the importance of evaluating and caring for individuals with endometrial hyperplasia.Methods: Studies examining the association between various factors such as diabetes mellitus, hypertension, age, estrogen replacement therapy, anovulatory disorders, smoking, medications, genetic factors, and endocrine-related proteins and the development of endometrial hyperplasia were reviewed. The literature search encompassed relevant databases, including PubMed, Scopus, and Web of Science.Results: Research findings indicate significant associations between changes in gene expression of several factors and the development of endometrial hyperplasia. Notably, the risk of progression to cancer varies between non-atypical and atypical hyperplasia cases. Factors such as diabetes mellitus, hypertension, age, estrogen replacement therapy, anovulatory disorders, smoking, medications, Lynch syndrome, tamoxifen use, and alterations in gene expression of TNF-α, EGF, IGF-1, IGF-1R, and PTEN have been implicated in the pathogenesis of endometrial hyperplasia.Conclusion: This study underscores the importance of understanding the factors influencing endometrial thickness during the perimenopausal period. It emphasizes the pivotal role of healthcare professionals in evaluating and caring for individuals with this condition.Keywords: endometrial hyperplasia, premenopausal period, postmenopausal women, pathogenesis, malignancy risk